2006
DOI: 10.1111/j.1365-2621.2006.tb12399.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption‐enhancing Treatments for Antihypertensive Activity of Oligopeptides from Tuna Cooking Juice: In Vivo Evaluation in Spontaneously Hypertensive Rats

Abstract: The aim of this study was to evaluate the absorption-enhancing effect for antihypertensive activity of an angiotensin I-converting enzyme (ACE) inhibitory oligopeptides in spontaneously hypertensive rats (SHR). The oligopeptides OA3, derived from tuna cooking juice, significantly reduced systolic blood pressure (SBP) in SHR at the doses of 0.5, 0.75, and 1.0 g/kg body weight; their efficacies were exhibited in a dose-dependent manner. Emulsification, microencapsulation, and lipophilization were applied to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…By referring to the method of Ko et al [ 18 ], MSJ was sealed in a vacuum bag and stored overnight in the refrigerator at 4 °C. The oil floated on top of the MSJ was removed by filtration and the mixture was centrifuged at 5000× g for 15 min (4 °C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By referring to the method of Ko et al [ 18 ], MSJ was sealed in a vacuum bag and stored overnight in the refrigerator at 4 °C. The oil floated on top of the MSJ was removed by filtration and the mixture was centrifuged at 5000× g for 15 min (4 °C).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many studies were conducted on protein hydrolysates in steaming juice. Findings indicated that salmon steaming juice was consisted of antioxidant, hypoglycemic, antihypertensive, anti-cancer, and other physiological activities [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In addition, mackerel steaming juice (MSJ) contained antibacterial, antioxidant, and other physiological activities [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the different approaches were feasible, the enhancing effect provoked by encapsulation in liposomes was more effective than those of surfactants and mucoadhesive substances. Liposomes at a half-dose of that of the non-encapsulated oligopeptides exerted a higher reduction in SBP and long-lasting effect in SHRs [103]. Later on, and with the aim of reducing cholesterol concentration in liposomes, the suitability of phytosterol instead of cholesterol for encapsulating tuna cooking juice oligopeptides was evaluated.…”
Section: Oral Delivery Strategiesmentioning
confidence: 99%
“…Antihypertensive activity of the strongest ACE-inhibiting fraction (OA3 oligopeptides) from orientase hydrolysate can be improved by encapsulated in liposomes (Ko, Cheng, Hsu, & Hwang, 2006). OA3 is composed of hydrophilic peptides with IC 50 = 0.21 mg protein/ml (Hwang & Ko, 2004).…”
Section: Introductionmentioning
confidence: 99%